2022
DOI: 10.3389/fmicb.2022.848536
|View full text |Cite
|
Sign up to set email alerts
|

Ms1 RNA Interacts With the RNA Polymerase Core in Streptomyces coelicolor and Was Identified in Majority of Actinobacteria Using a Linguistic Gene Synteny Search

Abstract: Bacteria employ small non-coding RNAs (sRNAs) to regulate gene expression. Ms1 is an sRNA that binds to the RNA polymerase (RNAP) core and affects the intracellular level of this essential enzyme. Ms1 is structurally related to 6S RNA that binds to a different form of RNAP, the holoenzyme bearing the primary sigma factor. 6S RNAs are widespread in the bacterial kingdom except for the industrially and medicinally important Actinobacteria. While Ms1 RNA was identified in Mycobacterium, it is not clear whether Ms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 77 publications
1
8
0
Order By: Relevance
“…We confirmed that scr3559 sRNA is an Ms1 homolog in S. coelicolor ( 37 ) (Figure 6A and B ) and RIP-seq also verified the first nucleotide of scr3559 (Figure 6E and F ) which we had determined by 5′ RACE previously ( 37 ). In exponential phase, scr3559 strongly interacted with RNAP (∼310-fold enrichment) and did not interact with HrdB (∼2-fold enrichment, Figure 6A and C , Supplementary Table S5 ).…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…We confirmed that scr3559 sRNA is an Ms1 homolog in S. coelicolor ( 37 ) (Figure 6A and B ) and RIP-seq also verified the first nucleotide of scr3559 (Figure 6E and F ) which we had determined by 5′ RACE previously ( 37 ). In exponential phase, scr3559 strongly interacted with RNAP (∼310-fold enrichment) and did not interact with HrdB (∼2-fold enrichment, Figure 6A and C , Supplementary Table S5 ).…”
Section: Resultssupporting
confidence: 84%
“…Nevertheless, mycobacteria are rod-shaped and unicellular, while streptomyces have a complex life cycle that starts with spore germination, then proceeds to a filamentous and highly branched vegetative (primary) mycelium, followed by formation of a secondary mycelium and eventually spores. Recently, there were contradictory results describing the presence of 6S RNA or an Ms1 homolog in Streptomyces coelicolor ( 30 , 31 , 37 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations